2019
DOI: 10.1111/aji.13208
|View full text |Cite
|
Sign up to set email alerts
|

Differential levels of surfactant protein A, surfactant protein D, and progesterone to estradiol ratio in maternal serum before and after the onset of severe early‐onset preeclampsia

Abstract: Problem Preeclampsia (PE), a multifactorial disorder characterized by impaired placental development, elevated inflammatory response and dysregulated placental steroidogenesis. PE may be preventable if predicted early on. Method of study The study evaluated the potential of immunomodulatory collectins, surfactant protein A (SP‐A), surfactant protein D (SP‐D), and mannose binding lectin (MBL), to predict PE before the disease onset, in a prospective study cohort of healthy pregnant women (n = 922). In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Sections were deparaffinized, rehydrated, and subjected to antigen retrieval (Vector Laboratories) treatment for 20 minutes followed by blocking the endogenous peroxidase with 3% hydrogen peroxide in methanol for 20 minutes. Horse serum (Vector Laboratories) was used for blocking the sections for 30 minutes at room temperature and incubated with Ki‐67 antibody (#VP‐RM04; Vector Laboratories, 1:100) or rabbit polyclonal anti‐human Sftpd antibody (1:500) antibody overnight at 4°C 25 . Sections were washed twice with 1× PBS and treated with biotinylated anti‐rabbit/mouse IgG secondary antibody (Vector Laboratories) for 45 minutes, followed by ABC reagent for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections were deparaffinized, rehydrated, and subjected to antigen retrieval (Vector Laboratories) treatment for 20 minutes followed by blocking the endogenous peroxidase with 3% hydrogen peroxide in methanol for 20 minutes. Horse serum (Vector Laboratories) was used for blocking the sections for 30 minutes at room temperature and incubated with Ki‐67 antibody (#VP‐RM04; Vector Laboratories, 1:100) or rabbit polyclonal anti‐human Sftpd antibody (1:500) antibody overnight at 4°C 25 . Sections were washed twice with 1× PBS and treated with biotinylated anti‐rabbit/mouse IgG secondary antibody (Vector Laboratories) for 45 minutes, followed by ABC reagent for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Horse serum (Vector Laboratories) was used for blocking the sections for 30 minutes at room temperature and incubated with Ki-67 antibody (#VP-RM04; Vector Laboratories, 1:100) or rabbit polyclonal anti-human Sftpd antibody (1:500) antibody overnight at 4°C. 25 Sections were washed twice with 1× PBS and treated with biotinylated anti-rabbit/ mouse IgG secondary antibody (Vector Laboratories) for 45 minutes, followed by ABC reagent for 30 minutes. Diaminobenzidine (Vector Laboratories) was used as a substrate to develop the stain.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…PE is an excessive inflammatory reaction of women to pregnancy. Previous reports have indicated that impaired angiogenesis, increased oxidative stress, and hormonal and immunological changes in placental microenvironment might be the causes of placental defects in preeclampsia 25 . Impaired placental development will lead to persistent hypoxia at the fetus-mother interface and increased systemic inflammatory response 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Preeclampsia is a multifactorial disease characterized by impaired placental development, enhanced inflammation, and disordered placental steroid production 25 . However, the diagnosis and treatment of preeclampsia are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that plasma or serum E2 concentrations were down‐regulated, whereas other studies reported that there were no significant changes in preeclamptic compared to normotensive pregnant women during the first and second trimesters. 17 , 18 , 19 The majority of published studies have shown the level of T in PE patients at different gestational weeks was generally high, but some reports indicated that there were no changes in the level of T in PE patients. 20 , 21 , 22 , 23 Aromatase (CYP19A) is a rate‐limiting enzyme for estrogen biosynthesis, which converts T into E2 in the placenta.…”
Section: Discussionmentioning
confidence: 99%